Fairness and Justice in the Procedure of the Iran–United States Claims Tribunal - Fatemeh Niavarani; Fathollah Rahimi; Tavakkol Habibzadeh (پژوهشهای حقوقی)
Justice and fairness are the greatest goals of legal proceedings both in international courts and tribunals and in domestic courts. Equity and fairness are the center of gravity of foreign investment law, which aims to increase the flow of capital globally and improve economic relations between countries. Attracting foreign investment through gaining trust in the administration of justice in the judicial and arbitration system is very important for economic growth. Fairness has different functions and concepts. Sometimes it is known as a general legal principle and sometimes as ex aequo et bono and sometimes it is seen as a code of conduct and in foreign investment agreements as fair and equitable treatment. The views of the Iran-United States Claims Tribunal, which is 40 years old, are very important in various investment issues and the approach of the tribunal, as one of the most influential arbitration authorities in the international arena, is the goal of this article; by searching the opinions of the Court, it aims to clarify the position of fairness, ex aequo et bono and fair and equitable treatment in the decisions of the tribunal. Relying on contractual law and international law, the tribunal has the authority to resort to equity, ex aequo et bono and fair and equitable treatment. But among the concepts and functions of fairness, only equity has been invoked by the tribunal as a legal principle.